Decentralized, Connectivity-Preserving, and Cost-Effective Structured Overlay Maintenance - Chen, Yu; Chen, Wei (Springer-Verlag, 2007)
In this paper we present a rigorous treatment to structured overlay maintenance in decentralized peer-to-peer (P2P) systems subject to various system and network failures. We present a precise specification that requires the overlay maintenance protocols to be decentralized, preserve overlay connectivity, always converge to the desired structure whenever possible, and only maintain a small local state independent of the size of the system. We then provide a complete protocol with proof showing that it satisfies the specification. The protocol solves a number of subtle issues caused by decentralization and concurrency in the system. Our specification and the protocol overcomes a number of limitations of existing overlay maintenance protocols, such as the reliance on a centralized and continuously available bootstrap system, the assumption of a known system stabilization time, and the need to maintain large local membership lists.